Environmental crime and the harm prevention criminalist - White, Rob (Frontiers in Conservation Science, 2022)
The role of the ‘pracademic’ comes in the fore in the interface between academia and environmental protection. This article explores the translation of evidence-based research and theoretical innovation in environmental crime prevention into ground level practice. Crime prevention as applied to illegal fishing forms the initial focus of the discussions. This is followed by discussion of pracademics and the importance of combining academic work and practitioner experience as part of applied criminology. The paper then discusses the potential role of a ‘harm prevention criminalist’ in crime prevention interventions. As something potentially at the frontier of future work, this position involves a combination of skills including site and crime assessment, interpersonal communication, collaborative engagement, and horizon scanning.